2019
DOI: 10.1038/s42255-019-0146-4
|View full text |Cite
|
Sign up to set email alerts
|

Metformin-induced increases in GDF15 are important for suppressing appetite and promoting weight loss

Abstract: Metformin is the most commonly prescribed medication for type 2 diabetes, owing to its glucose-lowering effects, which are mediated through the suppression of hepatic glucose production (reviewed in refs. 1-3). However, in addition to its effects on the liver, metformin reduces appetite and in preclinical models exerts beneficial effects on ageing and a number of diverse diseases (for example, cognitive disorders, cancer, cardiovascular disease) through mechanisms that are not fully understood 1-3. Given the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

23
163
2
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(226 citation statements)
references
References 47 publications
23
163
2
3
Order By: Relevance
“…Similarly, Chung et al (100) showed that induction of GDF-15 upon mitochondrial unfolded protein response (UPR mt ) activation was CHOP-dependent. Interestingly, metformin was reported to increase the expression of ATF4 and CHOP, further stimulating the secretion of GDF-15 in mouse and human hepatocytes (24). Therefore, current evidence indicates that metformin increases GDF-15 gene expression and stimulate GDF-15 secretion by direct induction of integrated stress response regulators ATF4 and CHOP.…”
Section: Metformin Induces Gdf-15 Via Atf4 and Chopmentioning
confidence: 90%
See 1 more Smart Citation
“…Similarly, Chung et al (100) showed that induction of GDF-15 upon mitochondrial unfolded protein response (UPR mt ) activation was CHOP-dependent. Interestingly, metformin was reported to increase the expression of ATF4 and CHOP, further stimulating the secretion of GDF-15 in mouse and human hepatocytes (24). Therefore, current evidence indicates that metformin increases GDF-15 gene expression and stimulate GDF-15 secretion by direct induction of integrated stress response regulators ATF4 and CHOP.…”
Section: Metformin Induces Gdf-15 Via Atf4 and Chopmentioning
confidence: 90%
“…Bodyweight is usually maintained through central nervous system (CNS) circuitry integrating peripheral metabolic feedback signals of either energy surplus or deficit (21,22). Studies have shown converging evidence that growth differentiation factor 15 (GDF-15) mediates metformin's effect on the gut-nervous system axis to decrease body weight (23)(24)(25)(26). GDF-15, a member of the transforming growth factor beta (TGF-b) superfamily, has many names indicating its multiple functions, including macrophage inhibitory cytokine (MIC)-1, non-steroidal antiinflammatory drug-inducible gene (NAG)-1, placental TGF-b (PTGF), prostate-derived factor (PDF), and placental bone morphogenetic protein (PLAB) (27).…”
Section: Introductionmentioning
confidence: 99%
“…We found an inverse correlation between GDF15 increase during pregnancy and FM gain in NW but did not see a relationship between GDF15 and gestational weight gain. Increases in GDF15 mediate adiposity resistance 32 and are linked to reductions in body weight 12,33,34 and in FM 35 . The effect of GDF15 on weight loss is thought to be associated with appetite reduction regulated by binding to the GDNF family receptor α-like (GFRAL) receptor in the hindbrain 32,36 .…”
Section: Discussionmentioning
confidence: 99%
“…It was recently demonstrated that an increase in circulating GDF15, in response to metformin treatment, promotes weight loss in a GFRAL-dependent fashion 18,19 . Given that prolonged exercise leads to circulating GDF15 levels comparable to the GDF15 levels reported following metformin treatment, it raises the intriguing possibility that exercise-induced increases in endogenous GDF15 mediate the effects of intense exercise on transient food intake suppression 20,21 .…”
Section: Main Textmentioning
confidence: 99%